A synonymous codon change alters the drug sensitivity of ΔF508 cystic fibrosis transmembrane conductance regulator. Issue 1 (3rd September 2015) - Bali, Vedrana; Lazrak, Ahmed; Guroji, Purushotham; Fu, Lianwu; Matalon, Sadis; Bebok, Zsuzsanna
ABSTRACT: Synonymous mutations, such as I507‐ATCÅATT, in deletion of Phe508 in cystic fibrosis transmembrane conductance regulator (ΔF508 CFTR), the most frequent disease‐associated mutant of CFTR, may affect protein biogenesis, structure, and function and contribute to an altered disease phenotype. Small‐molecule drugs are being developed to correct ΔF508 CFTR. To understand correction mechanisms and the consequences of synonymous mutations, we analyzed the effect of mechanistically distinct correctors, corrector 4a (C4) and lumacaftor (VX‐809), on I507‐ATT and I507‐ATC ΔF508 CFTR biogenesis and function. C4 stabilized I507‐ATT ΔF508 CFTR band B, but without considerable biochemical and functional correction. VX‐809 biochemically corrected ~10% of both of the variants, leading to stable, forskolin+3‐isobutyl‐1‐methylxanthine (IBMX)‐activated whole‐cell currents in the presence of the corrector. Omitting VX‐809 during whole‐cell recordings led to a spontaneous decline of the currents, suggesting posttranslational stabilization by VX‐809. Treatment of cells with the C4+VX‐809 combination resulted in enhanced rescue and 2‐fold higher forskolin+IBMX‐activated currents of both I507‐ATT and I507‐ATC ΔF508 CFTR, compared with VX‐809 treatment alone. The lack of an effect of C4 on I507‐ATC ΔF508 CFTR, but its additive effect in combination with VX‐809, implies that C4 acted on VX‐809‐modified I507‐ATC ΔF508 CFTR. Our results suggest that binding of C4 and VX‐809 to ΔF508 CFTR is conformation specific and provide evidence that synonymous mutations can alter the drug sensitivity of proteins.—Bali, V., Lazrak, A., Guroji, P., Fu, L., Matalon, S., Bebok, Z. A synonymous codon change alters the drug sensitivity of ΔF508 cystic fibrosis transmembrane conductance regulator. FASEB J. 30, 201‐213 (2016). www.fasebj.org